2009 9th International Symposium on Communications and Information Technology 2009
DOI: 10.1109/iscit.2009.5341078
|View full text |Cite
|
Sign up to set email alerts
|

A unified histogram and laplacian based for image sharpening

Abstract: An effective method with enhancement procedures is proposed for image sharpening. Histogram equalization and edge detecting procedures are applied to original images. The mean value, standard deviation, and signal to noise ratio are defined as the statistical index which specifies the brightness, resolution, as well as the sharpness of the image. From the result of output images, the brightness and the contrast of the images were enhanced simultaneously with the sharpness and clearness of the mesh which outwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…First, the outline of the finger is sharpened through the Laplacian filter and histogram equalization is carried out. 32 And then, through finding the largest circle, a bounding box is obtained and the nail plate ROI is extracted. Figure 6 illustrates the results of the experiment.…”
Section: The Proposed Systemmentioning
confidence: 99%
“…First, the outline of the finger is sharpened through the Laplacian filter and histogram equalization is carried out. 32 And then, through finding the largest circle, a bounding box is obtained and the nail plate ROI is extracted. Figure 6 illustrates the results of the experiment.…”
Section: The Proposed Systemmentioning
confidence: 99%
“…Thus, knowing the purpose of the image is important because making the right decision for which techniques to use is required [2]. The techniques in this research are based on the past research [2,3] which can be defined as the function below [1,11], respectively.…”
Section: Histogram Equalizationmentioning
confidence: 99%
“…The process for image filtering would filter noise, as a consequently the output image has different characteristic from the input [7]. For the desired result the filtering processes enhances and attenuates some qualities of the image [10].However, the sharpening filter used in this research is shown in equations below [1] respectively.…”
Section: Sharpening Filtermentioning
confidence: 99%